DIGITALIZATION IN INDIA PROSPECT AND CHALLENGES - Shubhangi Sudarshan Zende (Universitas Komputer Indonesia, 2022)
Digitalization is the process of converting information into a digital format as well as transaction of documents, money and many more through this. Digitalization is the outcome of innovation and technological advancement. So, we able to say that digitalization is the dynamic way of life in 21st Century. Digitalization transforms the human lives from lot of angles and empowers the society in a batter manner. Digitalization of India starts from the cashless society, where a pauper man to the industrialist are going cashless and trying the digital ways for the payments. Other than that, we are using lot for the security system and the Digital Controls. India is going Digital as now our complete records can be stored digitally (Digi Locker) so that government can avoid frauds and other activities that are harmful. Digitalization of India is nothing but making our daily life less dependent and devoid of human interaction with the help of technology. Now the entire world is in our mobile handsets. You can book a travel ticket, do shopping, chat with your loved ones across the globe and even share your views to the external world more freely and easily. This is the result of digitalization. To make the India Digitalize to create a digital infrastructure like a high-speed internet, mobile phone, shareable private space on a public cloud, and creating a safe and secure cyber space as a utility to every Indian citizen with digital literacy. This paper will discuss the prospect and challenges of digitalization.